Pediatric traumatic brain injuries in war zones: a systematic literature review - Aguirre, Alex S.; Rojas, Kenny; Torres, Alcy R. (Frontiers in Neurology, 2023)
Background: Pediatric casualties in war zones are a devastating consequence of armed conflicts, causing significant challenges for affected children. Especially in the context of poor access to care. The aim of this study is to understand traumatic brain injuries in this high-risk population and to identify and provide information for the stakeholders. Also, to recognize future severe long-term consequences and develop strategies to prevent them and minimize their burden while aiding in the management of these cases.Methods: We carried out a systematic literature review following PRISMA guidelines to identify publications discussing traumatic brain injuries in children in the context of war zones, and we analyzed all the collected data.Results: Our study showed that head injuries were the most common casualty in war zones; males and females were affected, and the mean age was 8-10. Most children were reported to be from Afghanistan, and blasts were the most common mechanism of injury. The mortality fluctuated from 3% to 47%.There is a lack of evidence-based information regarding the characterization, approach, and management of children with TBI in conflict zones. While the world finds ways to live in peace, 2 This is a provisional file, not the final typeset article there is an urgency to research, train, and deploy enough specialists to these areas, if governments are serious about improving outcomes for this population.